Neurotensin inhibits neuronal Na+, K+-ATPase activity through high affinity peptide receptor - López Ordieres, María Graciela (2000)
Neurotensin is a peptide present in mammalian CNS and peripheral tissues, which may play a major role in neurotransmission or neuromodulation, subserving diverse physiological functions. We studied the effect of added neurotensin on ATPase activities in synaptosomal membranes isolated from rat cerebral cortex. Neurotensin at 3 x 10-8-3 x 10-6 M concentration decreased 20-44% Na+, K+-ATPase activity but failed to modify Mg2+-ATPase activity; lower neurotensin concentrations (3 x 10-14-3 x 10-10 M) had no effect on enzyme activities. This inhibitory effect was abolished by neurotensin heating, by enzyme preincubation with neurotensin during periods exceeding 10 min, or by adding 1 x 10-6 M SR 48692, a high affinity neurotensin receptor antagonist. Levocabastine, which blocks low affinity neurotensin receptor, failed to alter enzyme inhibition by the peptide. It is suggested that the sodium pump may be a target for neurotensin effects at neuronal level involving the participation of high affinity neurotensin receptor. © 2000 Elsevier Science Inc.